Jan Dąbski – przewodniczący polskich delegacji w Mińsku i Rydze. Próba reinterpretacji postaci - Drozdowski, Mateusz (Instytut Historii PAN, 2024)
The article aims to shed light on the figure of Jan Dąbski, head of the Polish delegations, during the armistice and peace negotiations with Bolshevik Russia in Minsk (August–September 1920) and in Riga (September–October 1920). The author confronts various opinions on Dąbski with the source material and the most recent publications, uncovering deeper determinants of his views and motivations. The analysis leads to a clarifi cation and reinterpretation of Dąbski’s role in the discussed events. The author focuses primarily on the fi rst stages of the negotiations conducted on the truce in Minsk and Riga in 1920.
p. 33-57
Summary in English.
Keywords: Dąbski, Jan (1880-1931); Ioffe, Adolʹf Abramovich (1883-1927); Chicherin, Georgii Vasil'evich (1872-1936); Poland. Treaties, etc. Soviet Union, 1921 March 18; Treaty of Riga; Polish-Bolshevik War; Russo-Polish War, 1919-1920; diplomatic and consular service, Polish - Soviet Union; Poland - foreign relations - Soviet Union - 1900-1945